Blood and tissue HIV-1 reservoirs display plasticity and lack of compartmentalization in virally suppressed people - Marion Pardons; Laurens Lambrechts; Ytse Noppe; Liesbet Termote; Sofie De Braekeleer; Jerel Vega; Ellen Van Gulck; Sarah Gerlo; Linos Vandekerckhove (Nature Communications)
Abstract Characterizing the HIV-1 reservoir in blood and tissues is crucial for the development of curative strategies. Using an HIV Tat mRNA-containing lipid nanoparticle (Tat-LNP) in combination with panobinostat, we show that p24+ cells from blood and lymph nodes exhibit distinct phenotypes. Blood p24+ cells are found in both central/transitional (TCM/TTM) and effector memory subsets, mostly lack CXCR5 expression and are enriched in GZMA+ cells. In contrast, most lymph node p24+ cells display a TCM/TTM phenotype, with approximately 50% expressing CXCR5 and nearly all lacking GZMA expression. Furthermore, germinal center T follicular helper cells do not appear to harbor the translation-competent reservoir in long-term suppressed individuals. Near full-length HIV-1 sequencing in longitudinal samples from matched blood, lymph nodes, and gut indicates that clones of infected cells, including those carrying an inducible provirus, persist and spread across various anatomical compartments. Finally, uniform genetic diversity across sites suggests the absence of ongoing replication in tissues under treatment.